Campylobacter pylori gastritis: long term results of treatment with amoxycillin. Issue 3 (March 1989) - Oderda, G; Dell'Olio, D; Morra, I; Ansaldi, N
Abstract : To evaluate the efficacy of amoxycillin in eradicating Campylobacter pylori, endoscopic biopsy specimens were taken from the antral mucosa of 40 children with gastritis before, immediately after, and (in 30 patients) three months after treatment. Immediately after treatment 34 patients (85%) no longer had the organism in the mucosa, and the gastritis had healed in 23 (58%). Three months later the infection had recurred in 22 of 30 patients (73%), and the gastritis had relapsed in all of them. Significantly more children in whom C pylori recurred had family histories of peptic ulcer disease. The results suggest that amoxycillin alone is ineffective in the long term treatment of C pylori gastritis.